Model Test on the Vibration Reduction Characteristics of a Composite Foundation with Gravel Cushion under Different Seismic Wave Amplitudes - Yingying Zhao; Weiming Gong; Xianzhang Ling; Peng Li; Ziyu Wang; Hong Fan (Shock and Vibration)
Gravel cushions have been introduced as a practical and efficient seismic isolation technology to ensure the safety of nuclear power plants. This study investigated the seismic isolation effect of a gravel cushion by conducting a series of shaking table tests on a model foundation with a cushion built of three different types of graded aggregates (single-sized (2–5 mm), two-sized (2–5 mm:5–10 mm = 3 : 1), and continuously graded) under input El Centro seismic waves with three different peak accelerations (0.1 g, 0.2 g, and 0.3 g). The testing results showed that the seismic isolation effect of the gravel cushion increased with the peak seismic acceleration. The gravel cushion built with single-sized aggregates had better seismic isolation performance than gravel cushions built with two-sized or continuously graded aggregates. Under input seismic waves with 0.1 g peak acceleration, the single-sized aggregate gravel cushion still had a seismic isolation effect with a vibration reduction rate of approximately 11.81%, whereas the other two gravel cushions had no effect. Under input seismic waves with peak accelerations of 0.2 g and 0.3 g, all three gravel cushions had seismic isolation effects with vibration reduction rates of approximately 18.63% and 17.92%, respectively. An empirical model is proposed for predicting the vibration reduction rate of the cushion. Under input seismic waves with 0.3 g peak acceleration, the ultimate vibration reduction rate of the gravel cushion fell between 20.44% and 31.33%. The gravel cushion is an excellent option for nuclear power plant foundations with high requirements for seismic isolation, provided that the required bearing capacity is satisfied.